THU0240 Defective regulation by ATP-GATED ionotropic P2X7 receptor drives T follicular helper cell expansion in systemic lupus erythematosus. (15th June 2017) - Gualtierotti, R; Faliti, CE; Gerosa, M; Grassi, F; Meroni, PL
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease of unknown aetiology. The deregulated activation of T follicular helper (Tfh) cells in secondary lymphoid organs may play a pivotal role in the activation of B cells and production of autoantibodies. Both murine and human Tfh cells were shown to be sensitive to extracellular ATP via purinergic P2X7 receptor. P2X7 is a non-selective ionic channel that in the presence of high concentrations of ATP or prolonged stimulation opens to a pore permeable to molecules up to 900 Da and causes cell death. Mice deleted for P2rx7 show a significantly worsened outcome of pristane-induced SLE. Expansion of circulating Tfh (cTfh) cells has been correlated with increased levels of autoantibodies and more severe clinical manifestations in SLE. Objectives: Our aim was to investigate the possible role of P2X7 receptor activity in driving cTfh expansion in a cohort of SLE patients. Patients with primary antiphospholipid syndrome (PAPS) and healthy donors (HD) served as normal controls. Methods: Forty-two adult patients with SLE (SLEDAI >4), 14 patients with primary antiphospholipid syndrome (PAPS) and 34 sex- and age-matched healthy donors (HD) were included. Circulating Tfh cells were isolated as a CCR7loPD1+ cells. In 32 patients with SLE, we investigated permeability of Tfh cells to Yo-Pro-1 staining over time at FACS upon stimulation with the P2X7 selective agonist BzATP and the presence of a correlation (Spearman's rho) between Tfh cells expansion and Yo-Pro uptake. We analysed in vitro differentiation of CXCR5+PD1+ Tfh cells and sensitivity of this pathway to BzATP in CD4 naïve cells isolated from 4 SLE and 4 healthy donors in the presence of a mixture of Activin A and IL-12, with or without BzATP. Results: As previously reported, SLE patients had a significant expansion of the CCR7loPD-1+ cTfh cells [SLE (n=42): 38.3±12.8% versus HD (n=34]): 21.6±4.5%, ****p<0.0001]. There was no significant difference in the representation of cTfh cells between PAPS patients ([n=14] 22.6±6.6%) and HD (p=0.6714). The analysis of BzATP induced Yo-Pro-1 permeability revealed a significantly increased resistance to P2X7-mediated cell death in SLE patients as compared to HD and PAPS patients (fold increase of Yo-Pro-1-positive cells at 450 sec, HD [n=28]: 5±2.3%; SLE [n=32]: 3±1.7%, ****p=0.003; PAPS [n=14]: 5±2.9%, **p=0.0042). Furthermore, Spearman's rho showed a significant correlation between the percentage of cTfh cells and the degree of Yo-Pro uptake (r -0.37). In vitro generation of Tfh cells from HD naïve cells revealed a significant response to inhibition by BzATP, which was not present when SLE naïve cells were used. Conclusions: The CCR7loPD-1+ cTfh cells are significantly expanded in SLE but not PAPS patients compared to HD. The degree of expansion correlates with diminished sensitivity to P2X7-mediated cell death. This defective regulation is present also within in vitro differentiation of Tfh from naïve cells isolated from SLE patients. Our data suggest a selective defect of P2X7-mediated control of Tfh cell generation and expansion in SLE. Disclosure of Interest: None declared